Influence of movable B₄C-limiter on characteristics of RF discharge plasma in the Uragan-2M torsatron - Glazunov, G.P.; Lozin, A.V.; Konotopskiy, A.L.; Baron, D.I.; Beletskii, A.A.; Bondarenko, M.N.; Chechkin, V.V.; Dreval, M.B.; Grigor’eva, L.I.; Kozulya, M.M.; Maznichenko, S.M.; Moiseenko, V.E.; et al. (Вопросы атомной науки и техники, 2019)
A variant of the B₄C movable biased pumped limiter for the Uragan-2M torsatron is described. Some results of experiments with the limiter moved from the vacuum chamber wall to the central region of the plasma column in the work mode of Uragan-2M operation are reported. The effect of limiter-plasma interaction on parameters of the RF plasma discharges is discussed. Представлена удосконалена модель рухомого B₄C-лімітера торсатрону Ураган-2М. Викладені і обговорюються попередні результати, отримані в експериментах із взаємодії плазми імпульсних ВЧ-розрядів з лімітером при його русі до центральної області плазмового шнура. Представлена усовершенствованная модель подвижного B₄C-лимитера торсатрона Ураган-2М. Изложены и обсуждаются предварительные результаты, полученные в экспериментах по взаимодействию плазмы импульсных ВЧ-разрядов с лимитером при его движении к центральной области плазменного шнура.